An Adult Patient with Fontan Physiology: A TEE Perspective - Edward Gologorsky; Angela Gologorsky; Eliot Rosenkranz (Anesthesiology Research and Practice)
Fontan and Baudet described in 1971 the separation of the pulmonary and systemic circulations resulting in univentricular physiology. The evolution of the Fontan procedure, most notably the substitution of right atrial-to-pulmonary artery anastomosis with cavopulmonary connections, resulted in significantly improved late outcomes. Many patients survive well into adulthood and are able to lead productive lives. While ideally under medical care at specialized centers for adult congenital cardiac pathology, these patients may present to the outside hospitals for emergency surgery, electrophysiologic interventions, and pregnancy. This presentation presents a “train of thought,” linking the TEE images to the perioperative physiologic considerations faced by an anesthesiologist caring for a patient with Fontan circulation in the perioperative settings. Relevant effects of mechanical ventilation on pulmonary vascular resistance, pulmonary blood flow and cardiac preload, presence of coagulopathy and thromboembolic potential, danger of abrupt changes of systemic vascular resistance and systemic venous return are discussed.